KORELASI LOWER LIMB LEAN MASS TERHADAP DAYA LEDAK OTOT TUNGKAI PADA ATLET RENANG SUB-ELIT - Nur Muhammad Ibrahim Satya Haq; Nur Bawono, Mokhamad; Anita Kumaat, Noortje; Sudijandoko, Andun; Firmansyah, Awang (JURNAL ILMU KEOLAHRAGAAN, 2025)
Lower Limb Lean Mass (LLLM) represents the fat-free muscle mass in the lower extremities, which plays a crucial role in generating explosive power. This study aimed to analyze the relationship between LLLM and lower-limb explosive power in sub-elite swimmers. Thirty-three athletes participated (22 males, 11 females; age 17.36 ± 1.55 years, height 164.3 ± 7.57 cm, body mass 56.39 ± 7.58 kg, BMI 20.84 ± 2.1 kg/m²). LLLM was assessed using an InBody 270 body composition analyzer, while explosive power was evaluated through the Countermovement Jump (CMJ) test with Force-decks. Results demonstrated significant correlations between LLLM and jump height (p = 0.001; r = 0.553), peak power (p = 0.001; r = 0.821), and takeoff peak force (p = 0.001; r = 0.805). These findings indicate that LLLM contributes substantially to explosive performance, particularly during the start and turn phases in swimming. Therefore, LLLM may serve as a functional indicator for monitoring and designing training programs to enhance swimmers explosive capacity.